PENGARUH JINGLE IKLAN VIDEO SUNSILK CONDITIONER VERSI "RAMBUT GA KUSUT, GA LEPEK" DI YOUTUBE TERHADAP RESPON KOGNITIF KHALAYAK - Irsalina Fitri; Sylvie Nurfebiaraning (Dialektika, 2017)
Jingle is one of creative strategy in advertising. The use of songs that attract attention and contains a simple message about a product is one of the creative strategies that many advertisers use but not for personal care products such as shampoo. Sunsilk recently used jingle in one of Sunsilk Conditioner's advertising campaigns. Its not broadcasted in conventional media such as television and radio but are broadcasted on interactive media, Youtube. The rapid use of internet in Indonesia encourages Sunsilk to utilize Youtube as advertising media. This study would like to see the effect of jingle video ads on Youtube towards the cognitive response of audiences. This research is a quantitative research with descriptive data analysis using simple linear regression analysis technique, with 400 respondents using non probability sampling method and sampling is used on women Youtube users, aged 17-30 years. The results of descriptive data obtained by the score of sub variable memorability of 72.70%, meaningfulness of 82.80%, likeability of 80.17%, adaptability of 76.90%, protectability of 78.47%, message thought of 82.82%, Source oriented thought of 72.92% and ad execution thought of 77% means that all variables are well rated by the respondent based on the continuum line. Based on the regression test it was found that ad jingle influenced cognitive response of 0.797. Based on the hypothesis test (t test) its had significant effect on the cognitive response, and based on the coefficient value of determination found that it influenced cognitive response equal to 52,6%.